Distributed Ledger Technology and Secured Transactions : Note 3. Distributed Ledger Technology and Secured Transactions Framework - World Bank (World Bank, Washington, DC, 2020)
This Guidance Paper provides a primer on distributed ledger technology (DLT) and highlights the junctures at which this new technology meaningfully impacts secured transactions frameworks. The aim is to identify legal and regulatory hotspots, laying the groundwork for their detailed and exhaustive analysis, which is carried out in the two companion papers (Collateral Registry, Secured Transactions Law and Practice in the Age of Distributed Ledger Technology and Regulatory Implications of Integrating Distributed Ledger Technology in Secured Transactions Frameworks).